Etnomatematika Kerajinan Batu Nisan di Desa Allakuang Kabupaten Sidenreng Rappang: Eksplorasi Konsep Geometri dan Strategi Optimasi Produksi - Auliyani sudirman; Zulfiqar Busrah; Buhaerah; Andi Aras (Delta-Pi: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to identify ethnomathematical activities in tombstone crafts in Allakuang Village, analyze the geometric shapes of tombstones, and explain the production optimization strategies applied by craftsmen from an ethnomathematical perspective. The study uses a qualitative approach with a mathematical ethnographic design. Data were collected through observation, interviews, and documentation, then analyzed using the Spradley ethnographic model supported by GeoGebra modeling and optimization analysis using POM-QM for Windows. The results show that the ethnomathematical activities found include measuring, counting, locating, and designing. Women's tombstones contain the concepts of symmetry, reflection, irregular polygons, and right prisms, while men's tombstones contain the concepts of polynomial functions, definite integrals, Riemann sums, and volumes of solids of revolution. In addition, craftsmen apply efficiency strategies in the use of raw materials, work time, and labor that can be modeled through linear programming. This study concludes that the practice of making tombstones in Allakuang Village not only represents local cultural heritage, but also contains formal mathematical concepts that have the potential to be used as a source of contextual mathematics learning through an ethnomathematics approach. Keywords: Ethnomathematics, Tombstones, Geometry, Optimization, GeoGebra.